The Roles of Global Workers’ Education in the Transnational Movement - Jaeung Kim (Adult Education Research Conference, 2022)
This study analyzes the role of workers’ education at the global level in building a transnational labor movement through the case of the Global Labour University.
Keywords: Workers’ Education; Globalization; Transnational Movement; Praxis